Effects of Fish Meal and Easily Digestible Carbohydrate Supplementation in Complete Silage on Nutrient Intake of Young Male Kacang Goats - Paulus K. Tahuk; Venansius Leki; Oktovianus R. Nahak (Journal of Tropical Animal Science and Technology, 2026)
This study aimed to determine the effect of animal protein and easily digestible carbohydrate feed supplementation in complete silage on crude fat, crude fiber, and BETN consumption of young male kacang goats. This study was conducted in the experimental pen of South Kefamenanu Village, Kota Kefamenanu District, North Timor Tenggah Regency from August to October 2024. The livestock used were 9 young male Kacang goats aged 6-8 months. The study used an experimental method with a Completely Randomized Design (CRD) consisting of 3 treatments and 3 replications, namely: T1: Complete silage 45% + 25% ground corn + 15% pollard bran + 10% rice bran + 5% fish meal, T2: Complete silage 45% + 25% ground corn + 10% pollard bran + 10% rice bran + 10% fish meal, T3: Complete silage 45% + 25% ground corn + 10% pollard bran + 5% rice bran + 15% fish meal. The results showed that the highest crude fiber consumption was in treatments T3 and T2 (28.98 ± 2.64 g / head / day; 28.32 ± 2.99 g / head / day). The highest crude fat consumption was in treatment T3 (68.00 ± 8.04 g / e / day). The highest BETN consumption was found in treatment T2 (265.25±13.63 g/head/day). Statistical analysis showed that the treatment had no significant effect on crude fiber, crude fat, and BETN consumption. It can be concluded that complete silage fed to Kacang goats at 5%, 10%, and 15% levels yielded similar results on crude fiber, crude fat, and BETN consumption.